Contributing Factors to Organizational Success: A Case Study of McDonaldâ€™s - Xin Rou Chia; Daisy Mui Hung Kee; Sue Ting Khor; Kai Yee Chin; Tzyy Xian Lok; Hanouf Ali Almutairi; Majdi Anwar Quttainah; Hariharan Balakrishnan; Swati Kulkarni (International Journal of Tourism and Hospitality in Asia Pasific, 2020)
McDonaldâ€™s is one of the most successful fast food companies around the world. It has approximately 32,000 outlets located in 119 countries. Being a global and modern fast food company, McDonaldâ€™s has a clear vision, â€œto be the worldâ€™s best quick service restaurant experienceâ€. This paper presents the contributing factors which drive McDonaldâ€™s success being a global and modern fast food company. McDonaldâ€™s top management believes that job satisfaction and motivation are the contributing factors to the success of McDonaldâ€™s. McDonaldâ€™s has won many awards over the years for its employeesâ€™ engagement programs.